Molecular detection of bovine leukemia virus: A study in Colombia cluster (2016)
The Enzootic Bovine Leukemia (EBL) is caused by a virus of the Retroviridae family, the Bovine Leukosis Virus (BLV), affecting cattle of any age, sex, race and generates significant economic losses. The few molecular studies carried out in Colombia, are focus on dairy cattle. For that reason, the present work, was directed to detect VLB by molecular PCR test in cattle, for different farms and regions, in order to evaluate the relationship between the presence of VLB in animals, with the geographic location and bovine livestock.Out of a total 230 clusters animals organized by region of origin, 22.6 % of they were detected infected with VLB; ofthese, the Centre region had the highest number of infected animals (50.7 %). As for the production type, dairy cattle were the most likely to be infected by the VLB (50.7 %). Results indicate a significant relationship between the presence of virus, with the geographic location and type of production.These results, are important in order to formulate control and preventives programs by the government agencies of animal health.